Responder
Solutions for the equations are:
1. \( x = 14 \)
2. \( x = \frac{4}{3} \)
3. \( x = 3 \) and \( x = -3 \)
4. \( x = 3 \)
5. \( x = 4 \)
6. \( x = \frac{4}{3} \) and \( x = 1 \)
Solución
Sure, let's solve each of the given equations for \( x \) step by step.
---
### 1. \(\sqrt{x + 2} = 4\)
**Step 1:** Square both sides to eliminate the square root.
\[
(\sqrt{x + 2})^2 = 4^2 \\
x + 2 = 16
\]
**Step 2:** Solve for \( x \).
\[
x = 16 - 2 \\
x = 14
\]
**Solution:** \( x = 14 \)
---
### 2. \(3 \sqrt{x} = 2 \sqrt{3}\)
**Step 1:** Isolate the square root.
\[
\sqrt{x} = \frac{2 \sqrt{3}}{3}
\]
**Step 2:** Square both sides to eliminate the square root.
\[
(\sqrt{x})^2 = \left(\frac{2 \sqrt{3}}{3}\right)^2 \\
x = \frac{4 \times 3}{9} \\
x = \frac{12}{9} \\
x = \frac{4}{3}
\]
**Solution:** \( x = \frac{4}{3} \)
---
### 3. \(\sqrt{x^{2} + 7} - 4 = 0\)
**Step 1:** Isolate the square root.
\[
\sqrt{x^2 + 7} = 4
\]
**Step 2:** Square both sides to eliminate the square root.
\[
(\sqrt{x^2 + 7})^2 = 4^2 \\
x^2 + 7 = 16
\]
**Step 3:** Solve for \( x^2 \).
\[
x^2 = 16 - 7 \\
x^2 = 9
\]
**Step 4:** Take the square root of both sides.
\[
x = \pm 3
\]
**Verification:**
- For \( x = 3 \):
\[
\sqrt{3^2 + 7} - 4 = \sqrt{9 + 7} - 4 = \sqrt{16} - 4 = 4 - 4 = 0
\]
- For \( x = -3 \):
\[
\sqrt{(-3)^2 + 7} - 4 = \sqrt{9 + 7} - 4 = \sqrt{16} - 4 = 4 - 4 = 0
\]
Both solutions are valid.
**Solution:** \( x = 3 \) and \( x = -3 \)
---
### 4. \(\sqrt{x - 2} = 4 - x\)
**Step 1:** Recognize that both sides must be non-negative.
\[
\sqrt{x - 2} \geq 0 \quad \text{and} \quad 4 - x \geq 0 \\
x - 2 \geq 0 \Rightarrow x \geq 2 \\
4 - x \geq 0 \Rightarrow x \leq 4
\]
So, \( 2 \leq x \leq 4 \).
**Step 2:** Square both sides to eliminate the square root.
\[
(\sqrt{x - 2})^2 = (4 - x)^2 \\
x - 2 = 16 - 8x + x^2
\]
**Step 3:** Rearrange the equation.
\[
0 = x^2 - 9x + 18
\]
**Step 4:** Solve the quadratic equation.
\[
x = \frac{9 \pm \sqrt{81 - 72}}{2} \\
x = \frac{9 \pm \sqrt{9}}{2} \\
x = \frac{9 \pm 3}{2}
\]
So,
\[
x = \frac{12}{2} = 6 \quad \text{or} \quad x = \frac{6}{2} = 3
\]
**Step 5:** Check for extraneous solutions within the domain \( 2 \leq x \leq 4 \).
- **For \( x = 6 \):**
\( 6 \) is not within \( 2 \leq x \leq 4 \). Discard.
- **For \( x = 3 \):**
\[
\sqrt{3 - 2} = 4 - 3 \\
\sqrt{1} = 1 \\
1 = 1 \quad \text{(Valid)}
\]
**Solution:** \( x = 3 \)
---
### 5. \(\sqrt{3x + 13} - 1 = x\)
**Step 1:** Isolate the square root.
\[
\sqrt{3x + 13} = x + 1
\]
**Step 2:** Recognize that the right side must be non-negative.
\[
x + 1 \geq 0 \Rightarrow x \geq -1
\]
**Step 3:** Square both sides to eliminate the square root.
\[
(\sqrt{3x + 13})^2 = (x + 1)^2 \\
3x + 13 = x^2 + 2x + 1
\]
**Step 4:** Rearrange the equation.
\[
0 = x^2 - x - 12
\]
**Step 5:** Solve the quadratic equation.
\[
x = \frac{1 \pm \sqrt{1 + 48}}{2} \\
x = \frac{1 \pm \sqrt{49}}{2} \\
x = \frac{1 \pm 7}{2}
\]
So,
\[
x = \frac{8}{2} = 4 \quad \text{or} \quad x = \frac{-6}{2} = -3
\]
**Step 6:** Check for extraneous solutions within the domain \( x \geq -1 \).
- **For \( x = 4 \):**
\[
\sqrt{3(4) + 13} - 1 = 4 \\
\sqrt{12 + 13} - 1 = 4 \\
\sqrt{25} - 1 = 4 \\
5 - 1 = 4 \\
4 = 4 \quad \text{(Valid)}
\]
- **For \( x = -3 \):**
\( -3 < -1 \). Disregard.
**Solution:** \( x = 4 \)
---
### 6. \(\sqrt{4 - 3x} = 4 - 3x\)
**Step 1:** Recognize that both sides must be non-negative.
\[
\sqrt{4 - 3x} \geq 0 \quad \text{and} \quad 4 - 3x \geq 0 \\
4 - 3x \geq 0 \Rightarrow x \leq \frac{4}{3}
\]
Also, the expression under the square root must be non-negative:
\[
4 - 3x \geq 0 \Rightarrow x \leq \frac{4}{3}
\]
**Step 2:** Let \( y = 4 - 3x \). The equation becomes:
\[
\sqrt{y} = y
\]
**Step 3:** Solve for \( y \).
\[
\sqrt{y} = y \\
\sqrt{y} - y = 0 \\
\sqrt{y} (1 - \sqrt{y}) = 0
\]
So,
\[
\sqrt{y} = 0 \quad \text{or} \quad 1 - \sqrt{y} = 0 \\
y = 0 \quad \text{or} \quad y = 1
\]
**Step 4:** Substitute back \( y = 4 - 3x \).
- **For \( y = 0 \):**
\[
4 - 3x = 0 \\
3x = 4 \\
x = \frac{4}{3}
\]
- **For \( y = 1 \):**
\[
4 - 3x = 1 \\
3x = 3 \\
x = 1
\]
**Step 5:** Verify both solutions within the domain \( x \leq \frac{4}{3} \).
- **For \( x = \frac{4}{3} \):**
\[
\sqrt{4 - 3\left(\frac{4}{3}\right)} = 4 - 3\left(\frac{4}{3}\right) \\
\sqrt{4 - 4} = 4 - 4 \\
\sqrt{0} = 0 \\
0 = 0 \quad \text{(Valid)}
\]
- **For \( x = 1 \):**
\[
\sqrt{4 - 3(1)} = 4 - 3(1) \\
\sqrt{4 - 3} = 4 - 3 \\
\sqrt{1} = 1 \\
1 = 1 \quad \text{(Valid)}
\]
**Solution:** \( x = \frac{4}{3} \) and \( x = 1 \)
---
## Summary of Solutions
1. \( x = 14 \)
2. \( x = \dfrac{4}{3} \)
3. \( x = 3 \) and \( x = -3 \)
4. \( x = 3 \)
5. \( x = 4 \)
6. \( x = \dfrac{4}{3} \) and \( x = 1 \)
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución